Direct Expression of CPT1a Enables a High Throughput Platform for the Discovery of CPT1a Modulators - Jason Chen; Tuyen Tran; Anthony Wong; Luofei Wang; Pranavi Annaluru; Vibha Sreekanth; Samika Murthy; Laasya Munjeti; Tanya Park; Utkarsh Bhat; Glynnis Leong; Yumeng Li; et al. (Applied Biosciences, 2025)
Carnitine palmitoyltransferase 1 (CPT1), which catalyzes the rate-limiting step of fatty acid oxidation, has been implicated in therapeutic approaches to several human diseases characterized by aberrant lipid metabolism. The isoform-specific quantification of CPT1 activity is essential in the characterization of small molecule inhibitors of CPT1, but several existing means to quantify enzymatic activity, including the use of radioisotope-labeled carnitine, are not amenable to scalable, high throughput screening. Here, we demonstrate that mitochondrial extracts from Expi293 cells transfected with a CPT1a plasmid are a reliable and robust source of catalytically active human CPT1. Moreover, with a source of catalytically active enzyme in hand, we modified a previously reported colorimetric method of coenzyme A (CoA) easily scalable to a 96-well format for the screening of CPT1a inhibitors. This assay platform was validated by two previously reported inhibitors of CPT1a: R-etomoxir and perhexiline. To further demonstrate the applicability of this method in small molecule screening, we prepared and screened a library of 87 known small molecule APIs, validating the inhibitory effect of chlorpromazine on CPT1.